SIPN south: coordinating seasonal predictions of sea ice in the Southern Ocean - Massonnet, F; Ried, P; Lieser, JL; Bitz, C; Fyfe, J; Hobbs, W; Kusahara, K (., 2018)
Like many regions of our planet, the Antarctic is currently undergoing profoundenvironmental changes. Sea ice is a prominent element of this environment: it controls theheat, gas, mass and momentum exchanges between the atmosphere and the ocean. Seaice has been steadily expanding in the Southern Ocean since the late 1970s but hasdisplayed significant negative anomalies in recent years. Understanding and predicting howthe sea-ice cover develops over time scales as short as a season is important not only forscientists but also for stakeholders or teams organizing field campaigns. Despite all potentialapplications, there has been to date no overall assessment of the capabilities of currentprediction systems to forecast sea ice conditions at time scales of a season. This is the goalof SIPN South. SIPN South is a 2-yr project endorsed by the Year of Polar Prediction (YOPP)project. SIPN South aims at evaluating the skill of various forecast systems (statistical,dynamical) in predicting the regional summer conditions around the Antarctic continent. Inthis poster, we are presenting the very first coordinated austral sea ice prediction that willtake place in February 2018 (summer sea ice minimum).